Dental fluorosis severity in children 8-12 years old and associated factors - Saldarriaga, Alexandra [UNESP]; Rojas-Gualdrón, Diego; Restrepo, Manuel; Santos-Pinto, Lourdes [UNESP]; Jeremias, Fabiano [UNESP] (Sociedad Argentina de Investigacion Odontologica, 2021)
The aim of this study was to determine the frequency and severity of dental fluorosis (DF) and the association between severity and risk factors. In a cross-sectional study, 8-to 12-year-old children, born in a Colombian district, were evaluated according to the Thylstrup and Fejerskov Index (TFI) by two calibrated examiners. Molar Incisor Hypomineralization (MIH) and dental caries (DC) were also evaluated. Ordinal logistic regression was applied (p<0.05). Risk factors and lifestyle factors were collected using a questionnaire answered by parents. DF was detected in 76 (98.7%) of the children (average of 18.4 ±1.81 permanent teeth affected). Grade TF2 was the most frequently observed (34.8%); TF5 was observed in all age groups; TF6-TF7 were observed in 12-year-olds. No association was found between DF severity and DC (Odds Ratio (OR)=1.35; 95%CI: 0.56-3.26) or MIH (OR=1.39; 95%CI: 0.43-4.46). DF severity was significantly associated with use of an indoor wood stove for food preparation (OR = 9.34; 95%CI: 1.11-78.57) and use of a pea-sized volume of toothpaste (OR = 27.42; 95%CI: 1.57-477.36). Prevalence of DC was 38.1% and prevalence of MIH was 14.4%. In this population, the frequency of DF was high and severity was associated with use of an indoor wood stove for food preparation and toothpaste amount used during childhood.
Severidad de fluorosis dental y factores asociados en niños de 8-12 años de edad
Keywords: children; dental fluorosis; severity